The Integration of Local Wisdom and Islamic Law A Socio-Legal Study of Minangkabau Tradition between Customary Values and Modern Reform in the Perspective of Maqāṣid al-Syarī‘ah - Isra Mardi (JURNAL ILMU SYARIAH, 2026)
This study examines the integration of Minangkabau local wisdom and Islamic law from the perspective of maqāṣid al-sharī‘ah, using a socio-legal approach to explain how customary law (adat) and the Sharī‘ah interact in shaping a living Islamic legal system. The study is motivated by the growing need for a model of Islamic legal reform that can respond to contemporary social change without undermining the authority of the naṣṣ or disregarding the dynamics of local culture. Employing a normative qualitative design within a socio-legal and legal pluralism framework, the study draws upon documentary sources, including classical and contemporary works on uṣūl al-fiqh, maqāṣid al-sharī‘ah, the doctrine of 'urf (custom), Minangkabau customary documents, and scholarly literature on legal pluralism, communal asset governance, and Islamic legal reform. The data were analyzed through normative interpretation, conceptual analysis, and thematic synthesis to examine the interaction between naṣṣ, 'urf, maqāṣid al-sharī‘ah, and social institutions in Minangkabau society. The findings demonstrate that the philosophy of adat basandi syarak, syarak basandi Kitabullah represents an institutional mechanism that harmonizes customary values and Islamic legal principles through deliberative decision-making, dispute resolution, the management of harta pusaka tinggi (ancestral communal property), and communal asset governance oriented toward public welfare (maṣlaḥah). The study further argues that harta pusaka tinggi is more appropriately understood as milk al-jamā‘ah (communal ownership), and therefore should not be equated directly with the individual inheritance regime governed by farā'iḍ. From the perspective of maqāṣid al-sharī‘ah, modernization does not diminish the role of customary institutions but rather encourages institutional transformation, enabling Islamic law to adapt to contemporary social realities while preserving its normative foundations. The principal contribution of this study is the formulation of the Contextual Integration Model of 'Urf–Maqāṣid–Legal Pluralism as an analytical framework for Islamic legal reform that integrates the authority of naṣṣ, the objectives of the Sharī‘ah, social institutions, and cultural dynamics in developing a contextual, humanistic, and sustainable Islamic legal system. Keywords: Minangkabau Local Wisdom; Islamic Law; Maqāṣid al-Sharī‘ah; 'Urf; Legal Pluralism; Living Islamic Law.